Pengaruh Sosialisai Pajak, Sanksi Pajak Dan Kesadaran Membayar Pajak Terhadap Kepatuhan Wajib Pajak Umkm Di Kabupaten Kudus - Annisa Afra’ Rahmawati; Setyo Mahanani; Agus Triyani (Mahesa Research Center, 2023)
This research was conducted with the aim of examining the effect of Tax Socialization, Tax Sanctions and Awareness of Paying Taxes on MSME Taxpayer Compliance in Kudus City. Taxpayer compliance is a condition in which taxpayers comply with their tax obligations and do not violate applicable tax regulations. The number of MSMEs increases every year, but the level of compliance of MSME taxpayers with tax reporting is still low and tends to decrease in 2020 and 2021. This research uses quantitative research using survey methods in collecting data. The population in this study was 17,182 Micro, Small and Medium Enterprises (MSMEs) in the Kudus district who were registered with the Cooperative and MSME Office. Using 120 samples with simple random sampling method. Using descriptive statistical tests, data quality tests, classic assumption tests, multiple linear regression analysis and hypothesis testing. The results of this study indicate that the variable Tax Socialization has a positive and significant effect on MSME taxpayer compliance in Kudus City, Tax Sanctions have a positive and significant effect on MSME Taxpayer Compliance in Kudus City and Awareness of Paying Taxes has a positive and significant effect on MSME Taxpayer Compliance in the Kudus City